Marketing of NGV in Malaysia : with particular reference in Johor Bahru / Mohd Ghazali Anggang and Mohd Lutfi Nadzar - Anggang, Mohd Ghazali; Nadzar, Mohd Lutfi (2006)
Malaysia is blessed with the vast natural gas reserve and with the available technology this gas is used as a viable alternative to petrol. Despite the early introduction of NGV, motorists in general are not very keen to explore the opportunity simply because of lack of knowledge on the subject, wrong technical perception, lack of marketing promotion and no serious efforts on the part of the authority to promote NGV. Knowing all the concerns of the motorists as well as the limitation of the product we should be able to formulate a strategy on how to increase the use of NGV in Malaysia thus reducing the dependency on the petrol.